Aplikasi Pembelajaran Bahasa Isyarat Metode Dynamic Time Wrapping Menggunakan Microsoft Kinect - Ricky Lemido (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2018)
SLBN Sulsel is a school with special students who are deaf and speechless. Frequent errors in communication between teacher and students where the teacher uses official language and students use local sign language, so that the information provided is poorly understood by students. Researchers design applications using kinect that can help teachers provide sign language information that meets the standards. The author uses a dynamic time wrapping method which is a matching data movement. The system results that have been designed as much as 98.3% have gone well in the learning process and as much as 1.7% still need improvement.